Chapter 4. Integrated Pest Management - Peter J. Dittmar; Nicholas S. Dufault; Johan Desaeger; Jawwad Qureshi; Nathan S. Boyd; Mathews Paret (EDIS, 2021)
Chapter 4 of the Vegetable Production Handbook.